THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN WORKING WITH LACK OF ABILITY STUDENTS IN THE PRIMARY GRADE - Idiyeva Niginabonu Erkin qizi (The Conference Hub, 2025)
This article discusses the role and importance of ICT in modern education, working with students who are lazy, attention, memory, individual, interactive.
Keywords: Modern education, lazy, attention, memory, individual, interactive.